How social preferences shape incentives in (experimental) markets for credence goods - Rudolf Kerschbamer; Matthias Sutter; Uwe Dulleck (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2015)
Credence goods markets suffer from inefficiencies caused by superior information of sellers about the surplus-maximizing quality. While standard theory predicts that equal mark-up prices solve the credence goods problem if customers can verify the quality received, experimental evidence indicates the opposite. We identify a lack of robustness with respect to heterogeneity in social preferences as a possible cause of this and conduct new experiments that allow for parsimonious identification of sellers' social preference types. Our results indicate that less than a fourth of the subjects behave in accordance with the standard assumption on preferences, the rest behaving either in line with other forms of selfish or in accordance with different variants of non- selfish social preferences. We discuss consequences of our findings for institutional design and agent selection.
Keywords: C72; C91; D82; 330; Credence Goods; Expert Services; Social Preferences; Distributional Preferences; Other-Regarding Preferences; Behavioral Economics; Experimental Economics